Contemporary explanations for Sunan Nasaie: A study of sheikh Muhammad Ali Adam approach in his commentary Zakhirah al-’Uqba / Romzi Taleh - Romzi , Taleh (2016)
The purpose of this research is to study the methodology of Mohammad bin Ali Adam al-Ethiopi in his work, “Zahirah al-„Uqba fi Sharh al-Mujtaba”. This work consists of writings and lectures on Sunan al-Nasa‟i al-Sughra written by Imam al-Nasa‟i. The focus of this study is on the science of narration and analysis of texts applied in the work. This study also introduces Imam al-Nasa‟i‟s work, Sunan al-Nasa‟i, and its position among other books of hadith collections. The biography of Mohammad bin Ali Adam is also introduced based on authoritative sources of reference, besides interviews with his students and followers. This study uses an analytical approach in order to identify the methodology employed by Mohammad bin Ali Adam in his analysis of the hadiths in Sunan al-Nasa‟i, as well as criticisms directed towards him. In producing this study, the writer used the comparison method, by comparing the methods applied in Zahirah al-„Uqba and in al-Shanqiti‟s Shuruq Anwar al-Minan al-Kubra. Zahirah al-„Uqba is a contemporary study of Sunan al-Nasa‟i which is difficult to find nowadays. In order to produce this study, the author studied the hadiths with the utmost care. The uniqueness of this analysis is its thoroughness, introducing readers to the hadiths and the problems contained in Sunan al-Nasa‟i. The author was consistent with the method applied in the study. The author also referred to the study by al-Shanqiti that was written before Zahirah al‟Uqba. However, the author added a few points such as lataif al-isnad besides focusing on the differences between Sunan al-Nasa‟i and the original writing, al-Sunan al-Kubra. Results of the study show that the author focused on the academic issues contained in the writings without being influenced by the source of the various opinions. Harsh criticisms and insults towards other scholars are nowhere to be found in this work. Instead, the author shows respect to scholars who provided insight, as every student should do.